Young Adult Reports of the Victim–Offender Overlap in Intimate and Nonintimate Relationships: A Nationally Representative Sample. (March 2019) - Taylor, Bruce G.; Mumford, Elizabeth A.; Liu, Weiwei; Berg, Mark; Bohri, Maria
Little is known about the role of conflict management in explaining the victim–offender overlap. This article assesses the victim–offender overlap for adults (18-32) in intimate and nonintimate relationships, covering their relationship with their partner and with friends and acquaintances/strangers. Controlling for conceptually important variables, we explore whether different conflict management styles are associated with a respondent being in the victim-only, offender-only, both, or neither group (separately for verbal aggression, physical abuse for intimate and nonintimate relationships, and sexual abuse for intimate relationships). Data are from a nationally representative panel of U.S. households ( N = 2, 284 respondents of whom 871 women and 690 men report being in an intimate partnership). We observed a high degree of overlap between victimization and offending across our abuse measures. We found a range of modestly consistent set of risk factors, for example, conflict management styles and self-control, for the victim–offender overlap for partner and nonpartner abuse experiences.